2022
DOI: 10.3947/ic.2022.0069
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infections in Patients with Hematologic Diseases: Causative Organisms and Factors Associated with Resistance

Abstract: Background Patients with hematologic diseases are at high risk of bloodstream infections (BSIs). This study aimed to analyze clinical features and distributions of microorganisms in patients with hematologic diseases presenting at a tertiary care university-affiliated hospital in Korea. Materials and Methods We retrospectively reviewed all BSI episodes recorded in patient medical records at two hematologic wards of the Catholic Hematology Hospital from January to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The benefit of FQ prophylaxis in patients receiving HSCT is not standardized or consistent [ 31 , 32 , 33 ]. The results of a survey of Blood and Marrow Transplant Clinical Trials Network centers evaluating antibacterial antibiotic practices among 41 HSCT centers showed that FQ prophylaxis was used in 75% of the centers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of FQ prophylaxis in patients receiving HSCT is not standardized or consistent [ 31 , 32 , 33 ]. The results of a survey of Blood and Marrow Transplant Clinical Trials Network centers evaluating antibacterial antibiotic practices among 41 HSCT centers showed that FQ prophylaxis was used in 75% of the centers [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports highlight that bacterial infections are prevalent in patients with blood cancers [ 99 , 100 , 101 ], owing mainly to prolonged neutropenia during treatment [ 101 ]. Although patients with solid tumors are also susceptible to bacterial infections, an extensive epidemiological study reported an eightfold higher incidence in patients with hematological cancers than in patients with solid tumors [ 102 ].…”
Section: Bacterial Infections During Cancer Treatmentmentioning
confidence: 99%
“…Practical guidelines and clinical pathways for each infectious disease tailored to the characteristics of medical facilities are shared in a multifaceted manner to improve the treatment behavior of the medical facility in accordance with the guidelines and increase the frequency of appropriate initial empirical antimicrobial administration [ 47 48 49 ]. Prescription sets and checklists for best practice alerts can be used to incorporate treatment guidelines or policies into the prescription process [ 50 ].…”
Section: Core Elements Of Aspmentioning
confidence: 99%